James Mallinson y Mark Singleton (trad., ed. e introd.), Roots of Yoga, Londres, Penguin Books, 2017, 540 pp. - Muñoz, Adrián (Estudios de Asia y África, 2017)
James Mallinson y Mark Singleton (trad., ed. e introd.), Roots of Yoga, Londres, Penguin Books, 2017, 540 pp.